Tinjauan Hukum terhadap Perlindungan Hak Cipta atas Desain Busana di Kota Makassar: Studi Putusan No.1/Pdt.Sus-HKI/2020/PN Niaga Makassar - Asya Masrurah; Suhartati Suhartati; Nurmiati Nurmiati (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This research aims to analyze the forms of legal protection for copyright over fashion design and the judicial considerations applied in deciding copyright infringement in Putusan Pengadilan Niaga Makassar No. 1/Pdt.Sus-HKI/Cipta/2020/PN Niaga Makassar through a normative legal research method grounded in statutory and case approaches, where the findings demonstrate that fashion designs published through Instagram fulfill the elements of copyrightable works under Undang-Undang Nomor 28 Tahun 2014 tentang Hak Cipta because they meet the requirements of originality and fixation, thereby receiving automatic protection without the need for registration, while the Panel of Judges in the decision acknowledged the existence of copyright infringement based on substantial similarities between the plaintiff’s designs and the defendant’s uploads, yet the rejection of the plaintiff’s claim for compensation is considered insufficient to provide comprehensive legal protection because it does not restore the economic or moral losses suffered and fails to produce a deterrent effect for infringers, thus emphasizing the need to strengthen copyright protection in the digital era, particularly within the fashion industry, through judicial decisions that are more comprehensive, progressive, and responsive to technological developments and the increasing complexity of copyright violations.